If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23t + 5(1 + -5t) = 0 23t + (1 * 5 + -5t * 5) = 0 23t + (5 + -25t) = 0 Reorder the terms: 5 + 23t + -25t = 0 Combine like terms: 23t + -25t = -2t 5 + -2t = 0 Solving 5 + -2t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2t = 0 + -5 -2t = 0 + -5 Combine like terms: 0 + -5 = -5 -2t = -5 Divide each side by '-2'. t = 2.5 Simplifying t = 2.5
| 3t(3t)+5t-9=0 | | 2.5=8x | | -5(a+6)= | | 4069.44=3.14r^2 | | ab+4a+2b+8=0 | | 6(x)-(-10)=38 | | 6644.24=3.14r^2 | | 5c=10 | | 58+26= | | x+2+4+5+6+7+x+x+67=5 | | 25.12=2r*3.14 | | 28.26=3.14r^2 | | 4298.66=3.14r^2 | | 4298.66=2r*3.14 | | 4928.66=2r*3.14 | | 8+3x=33+x | | 4928.66=3.14r^2 | | 113.04=3.14r^2 | | 5x+23=8 | | 113.04=2r*3.14 | | 200=3x+5+15 | | 615.44=3.14r^2 | | 615.44=2r*3.14 | | 2y^2(3x^2)= | | 125.6=2r*3.14 | | 13.4w+12=5w-4 | | (17-9x+4x^2)-(7x-4x^2-28)= | | 12+3x+5y+4x-8y-89= | | 6358.5=3.14r^2 | | 4s^2+9s-28=0 | | 2x^2-12x+36=32 | | 6358.5=2r*3.14 |